Lincoln's defense of politics : the public man and his opponents in the crisis over slavery - Schneider, Thomas E., 1963- (University of Missouri Press, 2006)
"Examines six of Lincoln's key opponents (states' rights constitutionalists Alexander H. Stephens, John C. Calhoun, and George Fitzhugh; and abolitionists Henry David Thoreau, William Lloyd Garrison, and Frederick Douglass) to illustrate the broad significance of the slavery question and to highlight the importance of political considerations in public decision making"--Provided by publisher.